SOSIALISASI KURIKULUM MERDEKA BELAJAR SEBAGAI REFORMASI PENDIDIKAN MASA KINI - Yanti, Febri; Silalahi, Mastiur Verawaty; Situmorang, Masni Veronika (Jurnal Pengabdian Bukit Pengharapan, 2023)
Every school is currently preparing school teachers to understand and study the independent curriculum so that every teacher understands and teaches according to the curriculum that has been determined by the government. For this reason, the school invited lecturers as speakers to socialize what an independent curriculum is with the topic presented "Socialization of the Independent Learning Curriculum as Today's Education Reform". The purpose of community service carried out by lecturers by carrying out this outreach has a positive impact, namely for teachers, especially teachers at Surya Private High School, not only to teachers who have a good impact, but also to lecturers as speakers who also have an impact apart from building relationships with teachers at SMA. Private Surya also feels happy to be able to share knowledge.